2014
DOI: 10.1002/vnl.21402
|View full text |Cite
|
Sign up to set email alerts
|

Study on propylene polymerization in the presence of phenolic antioxidant (Irganox 1076) and characterization of stabilized polymers

Abstract: The aim of this study was to investigate different concentrations of Irganox 1076 on Ziegler-Natta catalyst performance during propylene polymerization. Antioxidant masking was conducted by addition of different molar ratio of triethylaluminum (TEAL). Proton nuclear magnetic resonance and Fourier transform infrared spectroscopy spectra confirmed the complete conversion of antioxidant to aluminum aryloxide form. The different concentrations of masked antioxidant with different molar ratio of TEAL were used duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The catalyst activity showed an increment when the additives were added into the reactor, however, by increasing the additive content above 25 mg the catalyst activity decreased. In addition, it is usually observed that the direct addition of additive to the Ziegler–Natta system decreases the activity of catalyst . Shen et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst activity showed an increment when the additives were added into the reactor, however, by increasing the additive content above 25 mg the catalyst activity decreased. In addition, it is usually observed that the direct addition of additive to the Ziegler–Natta system decreases the activity of catalyst . Shen et al .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of additives can also disturb monomer recovery process. Because of these technical problems which are not favorable from an industrial point of view, in recent years, few investigations have been reported on the use of antioxidants in the polymerization of propylene, and their effect and chemical structures on the activity of catalyst and properties of the final products. Antioxidants are categorized into primary and secondary classes.…”
Section: Introductionmentioning
confidence: 99%